GUIDANCE ON MEDICATION USE FOR DIABETIC AND HYPERTENSIVE PATIENTS IN RAMADAN: TOWARDS BETTER HEALTH OUTCOMES - Octavia, Devi Ristian; Winanda Putri, Amalia; Febriyanti, Amelia; Amelia, Artikasari Devi Putri; Alfi Novitasari, Hardiyanti (Universitas Muhammadiyah Lamongan, 2025)
Jubel Kidul Village in Lamongan Regency has a high prevalence of hypertension and diabetes mellitus. This is evidenced by the significant number of individuals purchasing antihypertensive and antidiabetic medications at local pharmacies and seeking treatment at healthcare centers for related complaints. This study aims to enhance public awareness of the importance of consistent medication adherence to reduce mortality associated with hypertension and diabetes mellitus. The community service employed educational interventions during the fasting month, focusing on proper medication use for hypertension and diabetes mellitus. These activities included guided counseling sessions and a final evaluation to assess the community’s level of understanding. Following the educational sessions and coaching, the final evaluation showed a marked improvement in participants’ knowledge compared to the pre-intervention assessment. Participants demonstrated comprehension and acceptance of the material delivered. The educational intervention effectively increased community knowledge regarding the correct use of medications during Ramadan, as evidenced by a significant rise in posttest scores. This suggests that targeted education can contribute to better health outcomes during the fasting period.